Water Diffusion In And Out Of The β-Barrel Of GFP and The Fast Maturing Fluorescent Protein, TurboGFP - Li, Binsen (2011)
The chromophore of fluorescent proteins is formed by an internal cyclization of the tripeptide 65SYG67 fragment and a subsequent oxidation. The oxidation is slow - the kinetics of this step is presumably improved in fast maturing GFPs. Water molecules can aid in the chromophore formation. We have used 50ns molecular dynamics simulations of the mature and immature forms of avGFP and TurboGFP to examine the diffusion of water molecules in-and-out of the protein β-barrel. Most crystal structures of GFPs have well-structured waters within hydrogen-bonding distance of Glu222 and Arg96. It has been proposed that they have an important role in chromophore formation. Stable waters are found in similar positions in all simulations conducted. The simulations confirm the existence of a pore that leads to the chromophore in the rapidly maturing TurboGFP; decreased water diffusion upon chromophore formation; and increased water diffusion due to the pore formation.